2015
DOI: 10.12943/anr.2015.00039
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Developing Subchannel Capability in an Advanced System Thermalhydraulic Code: A Literature Review

Abstract: In the framework of developing next generation safety analysis tools, Canadian Nuclear Laboratories (CNL) has planned to incorporate subchannel analysis capability into its advanced system thermalhydraulic code CATHENA 4. This paper provides a literature review and an assessment of current subchannel codes. It also evaluates three code-development methods: (i) static coupling of CATHENA 4 with the subchannel code ASSERT-PV, (ii) dynamic coupling of the two codes, and (iii) fully implicit implementation for a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The past research also provides perspectives for future directions. In the early phases of sub-channel thermal hydraulic analysis, the focus of research articles was mostly on analytical and experimental work done for the creation of sub-channel analysis codes, [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42]. These attempts were made to increase the accuracy of CFD predictions and to derive models from CFD for novel fuel geometries, decreasing the time needed for fuel assembly design and optimization, improving safety, and running the fewest number of tests possible to conserve resources and time.…”
Section: Introductionmentioning
confidence: 99%
“…The past research also provides perspectives for future directions. In the early phases of sub-channel thermal hydraulic analysis, the focus of research articles was mostly on analytical and experimental work done for the creation of sub-channel analysis codes, [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42]. These attempts were made to increase the accuracy of CFD predictions and to derive models from CFD for novel fuel geometries, decreasing the time needed for fuel assembly design and optimization, improving safety, and running the fewest number of tests possible to conserve resources and time.…”
Section: Introductionmentioning
confidence: 99%
“…They were developed for an improved description of the core thermal‐hydraulics using quasi‐3D models at component scale (decimeter to centimeter scale) for the prediction of local safety parameters such as critical heat flux (CHF) ratio, critical power ratio (CPR), fuel centerline temperature, and fuel surface temperature. A very detailed review of subchannel analysis methods and codes can be found in Moorthi et al and Cheng and Rao . In order to simulate the core thermal‐hydraulics of full cores using subchannel codes and to take profit from the increasing computer power, some subchannel codes were parallelized, eg, SCF and CORBA‐TF .…”
Section: Introductionmentioning
confidence: 99%
“…A very detailed review of subchannel analysis methods and codes can be found in Moorthi et al and Cheng and Rao. 23,24 In order to simulate the core thermal-hydraulics of full cores using subchannel codes and to take profit from the increasing computer power, some subchannel codes were parallelized, eg, SCF and CORBA-TF. 25 In addition, the codes using porous models to simulate the dedicated 3D porous media two-phase flow with a Cartesian or unstructured grid are being developed to overcome the usually 1D limitations of the system thermal-hydraulic codes.…”
Section: Introductionmentioning
confidence: 99%